International monetary cooperation since Bretton Woods - James, Harold 1956- (International Monetary Fund [u.a.], 1996)
This comprehensive account of the management of the international monetary system from the 1944 Bretton Woods conference to the present day documents the structure and movements of the world economy during a period of dramatic change. Commissioned by the International Monetary Fund to mark its fiftieth anniversary, the work is nevertheless a fully independent one: written by an outside historian with full access to IMF archives and staff, and reviewed by an independent editorial committee. An objective study of issues and events that are often controversial, the book skillfully interweaves the history of the IMF with that of world economic developments after the Second World War.
Keywords: Geschichte 1945-1995; BRETTON WOODS INSTITUTIONS; Economische samenwerking; Finances internationales; Financiële instellingen; INTERNATIONAL FINANCE; INTERNATIONAL FINANCIAL INSTITUTIONS; INTERNATIONAL MONETARY SYSTEM; Instituciones financieras internacionales; Institutions financières internationales; Internationale financiële politiek; Monetaire samenwerking; Politique monétaire - Coopération internationale; Política monetaria - Cooperación internacional; International finance; Monetary policy -- International cooperation; Financial institutions, International; Internationales Währungssystem